Risk Assessment of Potentially Toxic Heavy Metals in Wheat (Triticum aestivum L.) Grown in Soils Irrigated with Paper Mill Effluent - Mohssen Elbagory; Amal Zayed; Nagwa El-Khateeb; Sahar El-Nahrawy; Alaa El-Dein Omara; Ibrahim Mohamed; Marwa Yasien Helmy Elbyaly; Mahmoud El-Sharkawy; Jogendra Singh; Ana Dzaja; Boro Mioč; Ivan Širić (Toxics, 2025)
Unregulated irrigation with partially industrial effluents may lead to heavy metal contamination in crops and pose significant human health risks, especially in developing countries like India. Therefore, the present study aimed to quantify six heavy metals (Cd, Cr, Cu, Fe, Mn, and Zn) in soil and wheat irrigated with paper mill effluent, assess plant responses, and evaluate associated health risks for consumers. For this, a field study was conducted across ten sites (five effluent-irrigated, five borewell-irrigated as control), analyzing soil and wheat tissues for metal concentrations and calculating risk indices including bioaccumulation factor (Bf), translocation factor (Tf), Dietary Intake of Metals (DIM < 1), Health Risk Index (HRI < 1), and Target Hazard Quotient (THQ < 1). Results indicated high concentrations of Cd and Cr in effluent-irrigated soils and wheat tissues (root > stem > leaves > grains) compared to control sites, with some values exceeding permissible limits. Although the THQ values for heavy metals were below 1, indicating a low immediate health risk, concentrations of Cd and Cr in both soil and crop tissues exceeded acceptable safety standards. This study provides empirical evidence supporting the need for effluent treatment and policy interventions to mitigate agricultural contamination from the use of industrial effluents and protect public health.